Familial Normokalemic Periodic Paralysis Associated With Mutation in the SCN4A p.M1592V - Fu, Chao; Wang, Zhenyu; Wang, Libo; Li, Jia; Sang, Qiuling; Chen, Jiajun; Qi, Ling; Jin, Hui; Liu, Xiaoyang (Frontiers in neurology, 2018)
Periodic paralysis (PP) is an uncommon inherited disorder causing recurrent episodes of muscle weakness, with an incidence of 0.001%. Normokalemic periodic paralysis (NormoKPP) as the rarest subtype of PP contains both familial and sporadic. Familial NormoKPP caused by the p.M1592V mutation of the skeletal muscle sodium channel alpha subunit ( ) gene is rarely reported. Only three pedigrees of NormoKPP related to mutations in the p.M1592V have been previously reported. We herein presented a family case of NormoKPP associated with the p.M1592V mutation, in which respiratory muscle paralysis occurred in the proband while not in his children. Moreover, we conducted a thorough literature review. To our knowledge, this is the first report of respiratory muscle paralysis as a symptom of NormoKPP associated with mutation in the p.M1592V.